Straight allies: perceptions, beliefs, and identification - Smith, Sara Joanne (Kansas State University, 2011)
Individuals who associate with a stigmatized group may take on a “courtesy stigma”, and this may lead individuals to dissociate from stigmatized individuals for fear of also being stigmatized (Goffman, 1963). However many heterosexual individuals (i.e., straight allies) openly associate with lesbians and gay men (LG), and/or actively engage in LG social activism despite the risk of assuming a courtesy stigma. The current research examined the perceptions of and the identification processes associated with being straight allies. Results revealed that the willingness to take on a courtesy stigma may be influential in the process of straight ally identification. This research has implications for understanding the processes related to straight ally perceptions and identification. The current research will also promote general understanding of individuals who engage in prosocial behaviors despite possible negative consequences.
Keywords: Courtesy stigma; Straight allies; Psychology (0621)